Non-target mass spectrometry analysis of NDMA precursors in advanced treatment for potable reuse. Issue 12 (12th October 2018) - Roback, Shannon L.; Ferrer, Imma; Thurman, E. Michael; Ishida, Kenneth P.; Plumlee, Megan H.; Poustie, Andrew; Westerhoff, Paul; Hanigan, David
Abstract : Non-target high-resolution mass spectrometry was used to track the occurrence and removal of NDMA precursors during advanced treatment for reuse. Abstract : N -Nitrosodimethylamine (NDMA) is a disinfection by-product of concern in water reuse applications due to its potential human carcinogenicity. NDMA forms via the reaction of organic amine precursors with chloramines during water treatment. Advanced treatment for potable reuse reduces NDMA to non-detectable levels and removes most precursors. However, historical data from a full-scale potable reuse facility indicates NDMA can form after advanced treatment due to the presence of residual chloramine and NDMA precursors that are not removed during advanced treatment. This study used non-target high-resolution mass spectrometry to identify NDMA precursors and other trace organic compounds during advanced treatment for reuse. Inspection of the total ion chromatograms indicated that there was a substantial reduction of total ionizable compounds by reverse osmosis (RO). The RO feed water contained approximately 22 putative identifications of NDMA precursors across two sampling events. Only one of these precursors was found post-RO and none were found in the subsequent UV/advanced oxidation process (AOP) product water. In addition to the 22 NDMA precursors, the RO feed water contained 41 pharmaceuticals and pesticides that are not likely to be NDMA precursors. Similarly, these compounds were generally well removed by RO. Two compounds with unknown NDMA formation potential, one a suspected benzotriazole trimer with chemical formula C18 H16 N6 O3 and the other with an unassigned formula, were identified in the UV/AOP product water that were not present prior to UV/AOP (after RO), indicating they may be transformation products. Overall, this research demonstrates the utility of non-target analysis for water quality investigations.